Longer-term mortality and kidney outcomes of participants in the combination antibiotics for methicillin-resistant Staphylococcus aureus (CAMERA2) trial: a post hoc analysis - Legg, Amy (2023)
Background: The Combination Antibiotic Therapy for Methicillin-Resistant Staphylococcus aureus (CAMERA2) trial ceased recruitment in July 2018, noting that a higher proportion of patients in the intervention arm (combination therapy) developed acute kidney injury (AKI) compared to the standard therapy (monotherapy) arm. We analyzed the long-term outcomes of participants in CAMERA2 to understand the impact of combination antibiotic therapy and AKI. Methods: Trial sites obtained additional follow-up data. The primary outcome was all-cause mortality, censored at death or the date of last known follow-up. Secondary outcomes included kidney failure or a reduction in kidney function (a 40% reduction in estimated glomerular filtration rate to <60 mL/minute/1.73 m2). To determine independent predictors of mortality in this cohort, adjusted hazard ratios were calculated using a Cox proportional hazards regression model. Results: This post hoc analysis included extended follow-up data for 260 patients. Overall, 123 of 260 (47%) of participants died, with a median population survival estimate of 3.4 years (235 deaths per 1000 person-years). Fifty-five patients died within 90 days after CAMERA2 trial randomization; another 68 deaths occurred after day 90. Using univariable Cox proportional hazards regression, mortality was not associated with either the assigned treatment arm in CAMERA2 (hazard ratio [HR], 0.84 [95% confidence interval [CI],. 59-1.19]; P =. 33) or experiencing an AKI (HR at 1 year, 1.04 [95% CI,. 64-1.68]; P =. 88). Conclusions: In this cohort of patients hospitalized with methicillin-resistant S aureus bacteremia, we found no association between either treatment arm of the CAMERA2 trial or AKI (using CAMERA2 trial definition) and longer-term mortality.